2023
DOI: 10.1111/opo.13195
|View full text |Cite
|
Sign up to set email alerts
|

Emmetropic eye growth in East Asians and non‐East Asians

Abstract: PurposeTo compare axial length (AL) growth curves in East Asian (EA) and non‐EA emmetropes.MethodsA meta‐regression of 28 studies with emmetrope‐specific AL data (measured with optical biometry) was performed. Emmetropia was defined as spherical equivalent refraction (SER) between −0.50 and +1.25 D, determined under cycloplegia if the mean age was ≤20 years. The AL growth curve (mean AL vs. mean age) was first fitted to the full dataset using a weighted nonlinear mixed‐effects model, before refitting the model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Numerous studies have consistently established a strong association between myopia prevalence and grade levels ( 25–28 ), which can be attributed to heightened academic pressures, prolonged close-eye use, diminished engagement in outdoor activities, and sleep decrease as students progress to higher grades. The changes in ocular parameters that contribute to refractive error predominantly occur during childhood ( 29–31 ). In addition, the impact of COVID-19 on education and lifestyle has led to an increase in near-work activities and screen time, accompanied by a decrease in outdoor activities.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have consistently established a strong association between myopia prevalence and grade levels ( 25–28 ), which can be attributed to heightened academic pressures, prolonged close-eye use, diminished engagement in outdoor activities, and sleep decrease as students progress to higher grades. The changes in ocular parameters that contribute to refractive error predominantly occur during childhood ( 29–31 ). In addition, the impact of COVID-19 on education and lifestyle has led to an increase in near-work activities and screen time, accompanied by a decrease in outdoor activities.…”
Section: Discussionmentioning
confidence: 99%
“…Especially since recent research has shown that there is no evidence of physiological AL growth rates to be higher in East Asian eyes versus non-East Asian eyes, so we expect to be able to apply these physiological growth curves to East Asian eyes as well. 29 This paper aims to serve two purposes: 1. Since it is unknown whether AL growth is sufficiently inhibited by DIMS spectacle lenses to achieve the treatment goal of physiological AL growth, this paper reassessed first-year AL data from the above-mentioned study by Lam et al 14 using the AMMC system.…”
Section: Clinical Sciencementioning
confidence: 99%
“…Especially since recent research has shown that there is no evidence of physiological AL growth rates to be higher in East Asian eyes versus non-East Asian eyes, so we expect to be able to apply these physiological growth curves to East Asian eyes as well. 29 …”
Section: Introductionmentioning
confidence: 99%